Optimalisasi Visualisasi Produk Dapur 80 melalui Katalog Menu, Sticker dan Neon Box - Nur Rofiddatul Rofikoh; Dwi Ratna Pranatawati; Sekar Apriliana Kusumawati; Septa Fiqri Rizmawan; Dimas Setyanto; Ambar Istiyani (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
The purpose of this community service activity is to enhance the innovation and product visualization of the Micro, Small, and Medium Enterprise (MSME) Dapur 80 to increase consumer awareness and familiarity with its products. Through observations and interviews, several challenges were identified, including Dapur 80 lacked a consistent visual identity, used simple product packaging, had an unorganized menu, and did not have an appealing business location marker. To address these issues, the activity focused on designing and producing menu catalogs, product stickers, and a neon box—each playing a crucial role in enhancing product appeal. The results indicated successful implementation: catalogs were distributed to resellers, 100 stickers were printed and applied to product packaging, and one neon box was installed at the business location. An evaluation with the owner revealed satisfaction with the developed promotional media. Within just ten days of use, Dapur 80 recorded an increase of 11 new customers. However, the project was limited by its relatively short duration of one month, which constrained the measurement of long-term impacts. Despite this limitation, the community service activity contributed significantly to improving Dapur 80’s sales performance, demonstrating that enhanced product visualization can attract consumer attention, stimulate demand, and increase turnover.